Production and Operations Management / Total Quality and Resposiveness - Noori Hamid; Radford Russell (Mcgraw Hill Book Company, 1995)
Setting the Stage: Positioning for Quality, Satisfying the Customer, Designing and Building Fast-Response Organizations, Planning and Controlling in Fast-Response Organizations, A Look and a Look Forward, Appendices.
Setting the Stage: Positioning for Quality, Satisfying the Customer, Designing and Building Fast-Response Organizations, Planning and Controlling in Fast-Response Organizations, A Look and a Look Forward, Appendices.